2020
DOI: 10.1109/access.2020.3025164
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of COVID-19 Using Genetic Deep Learning Convolutional Neural Network (GDCNN)

Abstract: Rapid spread of Coronavirus disease COVID-19 leads to severe pneumonia and it is estimated to create a high impact on the healthcare system. An urgent need for early diagnosis is required for precise treatment, which in turn reduces the pressure in the health care system. Some of the standard image diagnosis available is Computed Tomography (CT) scan and Chest X-Ray (CXR). Even though a CT scan is considered a gold standard in diagnosis, CXR is most widely used due to widespread, faster, and cheaper. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 46 publications
0
54
0
Order By: Relevance
“…val. Acc 92.5, SEN 92 U U U H H Babukarthik et al [74] , Early diagnosis 102 GDCNN Imaging features unclear Acc 98.84, SEN 100, SPE 97.0 H H H H H Minaee et al [20] , Diagnosis unclear CNN Raw images without feature extraction TTS SEN 98, SPE 92 U U U H H Yan et al [94] , China, Diagnosis 206 CNN Imaging features TTS SEN 99.5 (95%CI: 99.3–99.7), SPE 95.6 (95%CI: 94.9–96.2) L H H H H Lokwani et al [95] , India, Diagnosis 55 NN Imaging features TTS SEN 96.4 (95% CI: 88–100), SPE 88.4 (95% CI: 82–94) U U H H H Jin et al [96] , China, Screening (early detection) 751 DL, DNN Imaging features TTS AUC 0.97, SEN 90.19, SPE 95.76 H U U H H Ko et al [29] , South Korea, Diagnosis 20 2D DL Imaging features TTS, ext.val. Acc 99.87, SEN 99.58, SPE 100.00 U U U H H Ezzat et al [34] , Diagnostic imaging 99 Hybrid CNN Not applicable TTS Acc 98 H U …”
Section: Resultsmentioning
confidence: 99%
“…val. Acc 92.5, SEN 92 U U U H H Babukarthik et al [74] , Early diagnosis 102 GDCNN Imaging features unclear Acc 98.84, SEN 100, SPE 97.0 H H H H H Minaee et al [20] , Diagnosis unclear CNN Raw images without feature extraction TTS SEN 98, SPE 92 U U U H H Yan et al [94] , China, Diagnosis 206 CNN Imaging features TTS SEN 99.5 (95%CI: 99.3–99.7), SPE 95.6 (95%CI: 94.9–96.2) L H H H H Lokwani et al [95] , India, Diagnosis 55 NN Imaging features TTS SEN 96.4 (95% CI: 88–100), SPE 88.4 (95% CI: 82–94) U U H H H Jin et al [96] , China, Screening (early detection) 751 DL, DNN Imaging features TTS AUC 0.97, SEN 90.19, SPE 95.76 H U U H H Ko et al [29] , South Korea, Diagnosis 20 2D DL Imaging features TTS, ext.val. Acc 99.87, SEN 99.58, SPE 100.00 U U U H H Ezzat et al [34] , Diagnostic imaging 99 Hybrid CNN Not applicable TTS Acc 98 H U …”
Section: Resultsmentioning
confidence: 99%
“…In addition to the basic information of patients, the vital signs, diagnoses and other lab tests are all time series. Existing many works [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]45] Besides, we have found that the time series of COVID-19 patients is irregularly sampled -Different time intervals exist in adjacent observations. Every possible test is not regularly measured during an admission.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning methods can train the parameters with complex nonlinearity to learn the data structures and have achieved state-of-the-art in many medical prediction tasks [19,20,47]. Thus, many current works apply deep learning methods for COVID-19 prediction tasks [28][29][30][31][32][33][34][35][36]. However, these methods either use the simple multi-layer perceptron for predicting or use the convolutional structures for image classification.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have focused on mortality predictions [ 9 ], diagnosis (identifying COVID-19 cases and differentiating them from other pulmonary diseases or no disease) [ 10 - 15 , 19 , 22 - 25 ], and severity assessment and disease progression [ 16 - 18 , 23 ]. Most current approaches have used deep learning methods and imaging features from CT scans [ 10 - 15 , 19 , 22 - 24 ] and X-ray imaging [ 18 , 20 , 21 ] with popular architectures including ResNet [ 10 , 12 , 14 , 23 ], U-Net [ 11 , 17 ], Inception [ 15 , 22 ], Darknet [ 20 ], and other convolutional neural networks (NNs) [ 18 , 21 , 26 , 27 ]. Recent reviews provide more details regarding these architectures [ 1 , 28 - 32 ].…”
Section: Introductionmentioning
confidence: 99%